HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG POSISI MENYUSUI DENGAN NYERI PUNGGUNG BAWAH HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG POSISI MENYUSUI DENGAN NYERI PUNGGUNG BAWAH - Yogie Erlangga Haq; dewi Anggraini; Ulfah Lesdilah (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction: Lower back pain is a musculoskeletal disorder in the lower back which is caused by poor body activity. The level of knowledge is a result of curiosity through sensory processes, especially in the eyes and ears for certain objects. Research Objectives To determine the relationship between the level of mother's knowledge about breastfeeding position and lower back pain at the Pondok Aren Health Center, South Tangerang City in 2021. This research method used a research design cross sectional. The sampling technique used Quota Sampling with the number of respondents 58 breastfeeding mothers. The results of the study obtained p value of 0.009(p value = 0.05), which means that Ha is welcome and can be concluded that the relationship level of knowledge of mothers about breastfeeding position with back pain at PHC Pondok Aren South Tangerang City 2021. Conclusion The results of their research on the correlation between mother's knowledge breastfeeding position with back pain at Pondok Aren Health Center, South Tangerang City in 2021.